Response to Cummins: The OHRC Right to Read Report will Move Ontario into the 21st Century - Klein, Perry (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2022)
In the April 2022 issue of the Journal of Teaching and Learning, Dr. Jim Cummins responded to the Ontario Human Rights Commission (2022a, 2022b) report on the Right to Read: Public Inquiry into Human Rights Issues Affecting Students with Reading Disabilities. He expressed several views on literacy education that are moderate and consistent with research. However, his very critical appraisal of the report is misdirected. The first section of the present article documents several recommendations and positions that Cummins attributes to the report but that it does not actually contain. The second section identifies five ways in which this report will bring Ontario’s special education policy into the 21st century, which Cummins has missed. The Right to Read report provides a paradigm for special education that Ontario should now apply to additional domains such as mathematics and social and emotional learning.